Pengaruh Suplementasi Nanomineral Zinc dalam Pakan terhadap Karakteristik Karkas Ayam KUB - Nova Larasati (Universitas Tidar, 2025)
The purpose of this study was to determine the effect of zinc (Zn) nanomineral supplementation in ration on carcass characteristics of Kampung Unggul Balai Penelitian dan Pengembangan Pertanian (KUB) chickens. The source of nanomineral zinc used was nano ZnO. This study used 200 KUB chickens. Each chicken in this study received one of the following five feed treatments: basal feed without added nanomineral Zn (NZ-0) or basal feed with the addition of 15 mg/kg (NZ-15), 30 mg/kg (NZ-30), 45 mg/kg (NZ-45), and 60 mg/kg (NZ-60). Each feed treatment was replicated four times with 10 chickens in each replicate cage. Treatment feed and drinking water were provided ad libitum during maintenance. Parameters observed in this study were live weight, carcass weight, carcass percentage, abdominal fat and abdominal fat percentage. Data were analyzed using analysis of variance based on a randomized complete block design. Each data variable with significant differences was further tested using Duncan's Multiple Range Test. The results showed that zinc nanomineral supplementation at the level of 45mg/kg feed increased live weight and carcass weight, and decreased abdominal fat and abdominal fat percentage.